1997
DOI: 10.1523/jneurosci.17-06-02030.1997
|View full text |Cite
|
Sign up to set email alerts
|

Early Developmental Destruction of Terminals in the Striatal Target Induces Apoptosis in Dopamine Neurons of the Substantia Nigra

Abstract: Many developing neural systems with peripheral projections depend on their target for trophic support during a critical period of natural cell death. Much less is known about central systems. That dopaminergic neurons of the substantia nigra may depend on their target, the striatum, during development is suggested by the presence of a natural apoptotic cell death event in these neurons that can be augmented by an early developmental axon-sparing striatal injury. To further assess the target dependence of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(131 citation statements)
references
References 43 publications
(64 reference statements)
9
122
0
Order By: Relevance
“…The extent of apoptosis in many central and peripheral neuronal populations, including midbrain DA neurons, depends on target innervation and/or trophic factor exposure. (Kelly and Burke, 1996;Haviv et al, 1997;Marti et al, 1997). Because GDNF has been demonstrated to be a target-derived trophic factor (Ström-berg et al, 1993;Tomac et al, 1995), it is more likely to exert survival-promoting activity on DA neurons during the time of target innervation rather than during earlier fetal development, when phenotypic differentiation occurs (Marti et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of apoptosis in many central and peripheral neuronal populations, including midbrain DA neurons, depends on target innervation and/or trophic factor exposure. (Kelly and Burke, 1996;Haviv et al, 1997;Marti et al, 1997). Because GDNF has been demonstrated to be a target-derived trophic factor (Ström-berg et al, 1993;Tomac et al, 1995), it is more likely to exert survival-promoting activity on DA neurons during the time of target innervation rather than during earlier fetal development, when phenotypic differentiation occurs (Marti et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…(Kelly and Burke, 1996;Haviv et al, 1997;Marti et al, 1997). Because GDNF has been demonstrated to be a target-derived trophic factor (Ström-berg et al, 1993;Tomac et al, 1995), it is more likely to exert survival-promoting activity on DA neurons during the time of target innervation rather than during earlier fetal development, when phenotypic differentiation occurs (Marti et al, 1997). Indeed, in situ hybridization studies have shown prominent GDNF mRNA expression in striatum during the first 2 postnatal weeks in the rat, the time during which connectivity between dopamine afferent fibers and striatal neurons develops in this species, and also the time period when the major apoptotic events occur in these neurons (Strömberg et al, 1993;Marti et al, 1997;Oo and Burke, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As envisioned by classic neurotrophic theory (Clarke, 1985;Barde, 1989), this death event appears to be regulated by target interactions; it is augmented by disruption of such interactions by a target lesion (Macaya et al, 1994), DA terminal destruction (Marti et al, 1997), or axotomy (El-Khodor and Burke, 2002) during the first 2 weeks of life. We have evaluated the possibility that GDNF may serve as a physiological, limiting, target-derived factor for SN DA neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Sections were mounted onto glass slides and lightly counterstained for Nissl substance using thionin to visualize nuclei and nucleoli. Apoptotic profiles were counted only if they fulfilled the criteria of having, in the same focal plane, both chromatin clumps within the nucleus together with TH-ir in the cytoplasm (Marti et al, 1997).…”
Section: Estimation Of Apoptosis Using Chromatin Clumpingmentioning
confidence: 99%